Work Place Related Issues in Health Sector: An Empirical Study With Reference To Selected Hospitals - Roja, K.; Kusuma, G. D.V.; Kumar, B. Ravi (American International Journal of Multidisciplinary Scientific Research, 2018)
The condition of working women in India as well as in the entire world in general is considered to be very distressing. Working women in general are subject to discrimination at various levels. The problems and difficulties of working women are multi-dimensional, varying from woman to woman at personal level, and section to section at general level and hence need to be analyzed in depth. There are very serious problems of wages, employment, income and standard of living and sexual harassment among working women. They are not able to get any advantage of social security schemes. Due to their ignorance and illiteracy they are not benefited from present welfare schemes. There has indeed been a growing realization that the women workers form an integral part of the process of national development. This has made the government make continuous effort to give women workers a better deal in spheres of work and to recognize their contribution to the socio-economic development of the Country. However, what has been done remains a drop in the ocean and the women worker remain exploited and unprotected working hours, conditions of work, wages, types of job and other situation is still not favorable to women workers. Women workers have many problems and problems of working women are more serious and server. The present study is an attempt to portray the work related issues in selected hospitals (i.e. GEMS, KIMS, RIMS, GMR).